Combining ability analysis for yield attributing traits in cytoplasmic male sterility based hybrids of Chilli (Capsicum annum ). (Current Horticulture, 2024)
Experiments were conducted to study the combining ability for yield attributing traits in CMS based hybrids of chilli (Capscum  annuum L.) at Vasantrao Naik Marathvada Krishi Vidyapeeth, Parbhani, Maharashtra, India. Sixteen parents and 60 F1 s  produced in line × tester mating design were used. The variance due to g,c,a and s,c,a were significant for all characters. The  fruit diameter of s,c,a variance were non - significant. The parents, BSPRL-171, BSPRL-066, BSPRL-188, Phule Jyoti, Pusa  Sadabahar, PBNC-1, and Parbhani Tejas, were good general combiner for fruit and yield. Hybrids, BSPRL-066 × Phule Jyoti,  BSPRL-171 × Phule Jyoti, BSPRL-171 × Bydagi, BSPRL-171 × G-4, BSPRL-226 × Kokan Kirti and BSPRL-189 × Bydagi had good  s,c,a effects for fruit and yield.
Keywords: Combining ability; Line × Tester analysis; Hybrids; Genotypes